Multiplicity of Quasilinear Schrödinger Equation - Xiaorong Luo; Anmin Mao; Xiangxiang Wang (Journal of Function Spaces)
In this paper, we study the quasilinear Schrödinger equation involving concave and convex nonlinearities. When the pair of parameters belongs to a certain subset of ℝ2, we establish the existence of a nontrivial mountain pass-type solution and infinitely many negative energy solutions by using some new techniques and dual fountain theorem. Recent results from the literature are improved and extended.